Evaluating an Aboriginal community controlled residential alcohol and other drug services: Use of benchmarking to examine within treatment changes in wellbeing. (1st February 2022) - Kelly, Peter J.; Coyte, Joe; Robinson, Laura D.; Deane, Frank P.; Russell, Sophie; Clapham, Kathleen; Dale, Elizabeth; Longbottom, Marlene; Solley, Ryan; Baker, Amanda L.
Abstract: Introduction: Aboriginal Community Controlled Organisations (ACCO) have an important role in the Australian health‐care sector. However, there has been a lack of research evaluating ACCOs in the treatment of alcohol and other drug (AOD) use. Using a benchmarking approach, the present study examined within treatment changes on measures of wellbeing for people attending a residential AOD ACCO. Methods: The study focused on The Glen, an AOD residential treatment service that is managed by the Ngaimpe Aboriginal Corporation ( n = 775). The Glen is a male‐only service and provides treatment to both Indigenous and non‐Indigenous men. The evaluation focused on measures of wellbeing (i.e. symptom distress and quality of life) collected at intake, 30 and 60 days during the person's stay. Comparative benchmarking was conducted with a cohort of men who were attending non‐ACCO residential AOD treatment services ( n = 4457). Results: The Glen participants demonstrated statistically significant improvements on measures of wellbeing. The Glen participants were more likely to complete treatment than participants attending non‐ACCO services. Likewise, Indigenous people attending The Glen were more likely to complete treatment (compared to Indigenous people attending non‐ACCO services). Rates of reliable and clinically significant change suggested that changes in quality of life were largely equivalent between The Glen and non‐ACCO services, while participants attending The Glen tended to demonstrate larger reductions in symptom distress compared to the non‐ACCO services. Discussion and Conclusion: The study provides further support for the important role that ACCOs play in supporting Indigenous people in their recovery.